Association of Maternal Dietary Habits and MTHFD1 Gene Polymorphisms With Ventricular Septal Defects in Offspring: A Case-Control Study - Xinli Song; Yiping Liu; Tingting Wang; Senmao Zhang; Mengting Sun; Jing Shu; Jianhui Wei; Jingyi Diao; Jinqi Li; Yihuan Li; Letao Chen; Ping Zhu; et al. (Frontiers Media S.A., 2022)
ObjectivesThis study aimed at assessing the association between maternal methylenetetrahydrofolate dehydrogenase 1 (MTHFD1) gene polymorphisms, maternal dietary habits, and their interactions with the risk of ventricular septal defects (VSD) in offspring.MethodsFrom November 2017 to March 2019, a case-control study comprising 360 mothers of VSD cases and 504 mothers of healthy infants was conducted in Han Chinese populations. The main exposures of interest were maternal dietary habits in early pregnancy and MTHFD1 gene polymorphisms. Logistic regression models were used to estimate the main effects and interaction effects.ResultsIt was observed that maternal excessive intake of pickled vegetables (aOR = 1.85, 95%CI: 1.45-2.37), smoked foods (aOR = 1.93, 95%CI: 1.48-2.51), barbecued foods (aOR = 1.74, 95%CI: 1.28-2.36), and fried foods (aOR = 1.68, 95%CI: 1.30-2.17) were associated with a higher risk of VSD in offspring, whereas maternal excessive intake of fresh meat (aOR = 0.61, 95%CI: 0.47-0.79), fish and shrimp (aOR = 0.29, 95%CI: 0.23-0.38), fresh eggs (aOR = 0.54, 95%CI: 0.42-0.70), fresh fruits or vegetables (aOR = 0.44, 95%CI: 0.33-0.60), soy foods (aOR = 0.65, 95%CI: 0.53-0.80), and milk products (aOR = 0.49, 95%CI: 0.40-0.59) could contribute significantly to a lower risk of VSD in offspring. Furthermore, the genetic polymorphisms of maternal MTHFD1 gene at rs1950902 (GA vs. GG: aOR = 0.67, 95%CI: 0.50-0.90) and rs2236222 (GG vs. AA: aOR = 2.75, 95%CI: 1.57-4.83) were significantly associated with the risk of VSD in offspring. In addition, there was a significant interaction effect between maternal dietary habits and MTHFD1 gene polymorphisms on the risk of VSD.ConclusionsMaternal dietary factors, MTHFD1 genetic polymorphisms, and their interactions were all associated with the risk of VSD in offspring. However, further research in diverse ethnic populations and with a larger sample size is warranted to corroborate our findings.Trial RegistrationRegistered in Chinese Clinical Trial Registry Center; registration number, ChiCTR1800016635; registration date, 06/14/2018 (Retrospectively registered); URL of trial registry record, https://www.chictr.org.cn/showproj.aspx?proj=28300.